Synthesis and Characterization of Holmium Oxide Doped Zinc Lead Borate Glasses - Alemi, Abdolali; Sedghi, Hassan; Mirmohseni, Abdolreza; Golsanamlu, Vali (Asian Journal of Chemistry, 2010)
Holmium doped zinc-lead borate glasses were prepared from melting in appropriate proportions of ZnO, PbO2, H3BO3 and (1-2 mol %) Ho2O3 mixture in the temperature range of 800-850ºC. The density of glass samples was measured using Archimedes´ principle. The infrared spectra of the glasses in the range of 4000-400 cm-1 showed their structure systematically. No boroxol ring formation was observed in the structure of these glasses but the conversion of three-fold to four-fold coordination of boron atoms in the structure of glasses was observed. Glass transition studies were done through differential scanning calorimetry. Optical analysis was done by using Judd-Ofelt theory.